Peningkatan Literasi Kewirausahaan Siswa SMK Husada Persada Indonesia di Kota Bekasi - Zahran, Wahidin Septa; Rahmat Setiawan, Dodi; Pentanurbowo, S.; Tamba, Rousdy Safari; Irwansyah, Iwan; Zulkipli, Zulkipli (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
The spirit of entrepreneurship needs to be instilled in the younger generation of millennials, so that it inspires the Stiami Institute Lecturers to carry out services in terms of entrepreneurial literacy to Persada Husada Indonesia School Bekasi City Students. This PKM aims; (1) To provide understanding and knowledge to students of SMK Persada Husada Indonesia Bekasi City about Entrepreneurship; (2) To provide stimulus to Persada Husada Indonesia Bekasi City students in an effort to increase their interest in entrepreneurship. Problems faced; (1) Lack of understanding of entrepreneurship; and (2) Still low interest in entrepreneurship To solve these problems comprehensively, assistance from various parties is needed. In this case, the Lecturers of the Stiami Institute of Social and Management Sciences have the responsibility to participate in solving the above problems, among others through community service programs.The methods used in solving the problem are; (1) Lecture; (2) Discussion; (3) Question and Answer; (4) Evaluation. A comparative des of students understanding and knowledge before and after participating in this activity, in general it is known that there was an increase in paticipants’ understanding and knowledge based on the results in table 1.The results achieved in the implementation of this PKM are: 1. Students have knowledge about Entrepreneurship. 2. Students have knowledge related to entrepreneurial characters, 3. Students are motivated to be involved in the world of entrepreneurship.